Steering bio-electro recycling of carbon dioxide towards target compounds through novel inoculation and feeding strategies. Issue 4 (August 2021) - Blasco-Gómez, R.; Romans-Casas, M.; Bolognesi, S.; Perona-Vico, E.; Colprim, J.; Bañeras, L.; Balaguer, M.D.; Puig, S.
Abstract: New strategies in inoculation and operation of bioelectrochemical systems were used to advance in the steering of bio-electro carbon dioxide (CO2 ) recycling towards chemical compounds. First, the preparation of microbe coated biocathodes ex-situ with putative electroactive species with CO2 as sole carbon source was assayed. Second, CO2 feeding strategies for the operation of BES systems were explored to ensure enough reducing power during batch mode operation. The impact on the proposed changes on the product portfolio and production yields was assessed. The initial enrichment of a putative electroactive community on bare electrode surfaces was proven to be successful and led to a shortening of the start-up period of the system from days to hours. Moreover, the establishment of a new feeding procedure to favor the presence of elevated reducing power availability for cells triggered the production of longer carbon chain carboxylates (max. 0.99 gbutyrate m −2 electrode d −1 ) and alcohols (max. 0.83 gethanol m −2 electrode d −1 ) at early stages of experiment. This work complements the recent knowledge on the control of bioelectrochemical processes by the establishment of strategies to obtain target added-value compounds from CO2 . Graphical Abstract: ga1 Highlights: New protocol for ex-situ enrichment of electroactive species on carbon cloth. The new inoculation strategy shortened start-up period from days to hours. Novel feeding strategy favored the production of longer carbon-chain chemicals.